Endodontic management of dens invaginatus using dynamic navigation system in pediatric patient: A case report - FATHIMA, Ayesha S.; SELVAGANESH, Sahana; JEEVANANDAN, Ganesh; SOLETE, Pradeep; MAGANUR, Prabhadevi C.; SYED AHMED, Ather; VISHWANATHAIAH, Satish (International Arab Journal of Dentistry (IAJD), 2025)
Dens invaginatus, also known as dens in dente, is a dental anomaly resulting from infolding of the enamel organ into the dental papilla. Dynamic Navigation Systems (DNS), like Navident, offer real-time guidance during endodontic procedures, proving especially useful in complex cases, such as calcified canals or pulp obliteration. This case report presents a 13-year-old female who reported the chief complaint of continuous pain in the upper left front tooth region. Based on the clinical and radiographic findings, a diagnosis of pulp necrosis and chronic periapical abscess in relation to maxillary canine (23) was established, with a dens invaginated palatal canal (Oehler’s type III). Despite CBCT imaging and analysis of canal morphology, difficulty in accessing the palatal canal orifice was encountered. Minimally invasive access with zero deviation from the original plan of negotiating the canal and without iatrogenic errors was achieved using a dynamic navigation system. This system was a valuable tool because it reduced chairside time, improved patient comfort, and, more importantly, completed the procedure without the risk of iatrogenic damage to the tooth structure.